Kemampuan Penalaran Matematis Siswa SMK Pada Materi Peluang - Shafiya Fadhila; Nita Hidayati (Universitas Batanghari Jambi, 2022)
The purpose of this study is describing students' mathematical reasoning abilities and to determine the level of students in working on problems on probability material. The method of this research is a descriptive research with a qualitative approach. Subjects for this study are 17 students of class XI from SMK Negeri 1 Rawamerta. The data collecting technique is that students are given a number of 4 item description questions as a written test and the selected subject will be interviewed. The results of this study found that students who have high reasoning abilities tend to use their own methods in solving problems of probability material. While students with low abilities cannot solve problems of probability if there is no formula and also students cannot write down information or draw conclusions from the results they got. In conclusion, mathematical reasoning ability is very important in working on problems with probability material.